Reviving firozabad's glass legacy: skill development for the preservation of artisanal craftsmanship. - Srivastava, Ayushi. (SPA Bhopal, 2024)
The rich heritage of Firozabad's glass industry, spanning centuries, stands as a testament to India's cultural and economic legacy. However, in the face of modernization and globalization, this esteemed craft faces the risk of fading into obscurity. This thesis delves into the comprehensive revitalization of Firozabad's glass legacy through a meticulous approach to skill development aimed at preserving artisanal craftsmanship. The project begins with an exploration of the cultural significance of glassmaking in India, highlighting its integral role in the country's diverse heritage. It examines the challenges posed by contemporary forces such as industrialization and globalization, which threaten the traditional practices and livelihoods of artisans. Through a detailed analysis of Firozabad's glass industry, including its historical evolution and current socio-economic landscape, the thesis identifies key areas for intervention. It proposes the establishment of a skill development center equipped with design innovation facilities and vocational training programs. These initiatives aim to empower artisans with the necessary skills and knowledge to adapt to changing market dynamics while preserving their cultural heritage. Furthermore, the thesis advocates for the creation of an efficient institutional framework to support the sustainability of Firozabad's glass industry. This framework seeks to mitigate exploitative practices and promote inclusive growth within the artisan community. By fostering awareness, promoting tourism, and facilitating direct market connections, the project aims to create a conducive environment for the revitalization of Firozabad's glass legacy. Through these multifaceted efforts, it aspires to uphold the tradition of glass craftsmanship while fostering economic and cultural resurgence in the region. Keywords:- Glass legacy, Skill development, Artisanal craftsmanship, Preservation.
Holistic Healing
Keywords: Architecture; Glass-Lagecy.